Study of e-Tendering Solution Implemented by Government of Goa - Gaurav, A. Naik; Korgaonkar, Vinita (International Journal of Computer Sciences and Engineering, 2022)
The paper focuses a comprehensive review on implementation of e-Tendering solution in comparison to the conventional envelop-Box (manual Tendering) method in the State of Goa (India). Some of the key issues like Comparative analysis of pre-deployment and post deployment scenarios with the launch of e-Tendering Solution, highlighting the day-to-day problems faced by the System Users. And also, to consider the best practices that can be followed in improving rollout of e-Tendering solution. The study inferred that in spite of several challenges, how Vendors/Contractors and Departmental Users has accepted the e-Tendering system over manual tendering. This research paper is based on the descriptive and exploratory methods used for analysis of collected responses as the primary data for the study from Vendors/Contractors and Departmental Users through the online mode. This paper has targeted the end user of the e-Tendering solution their day-to-day issues and challenges and describing the advancement made by the Government for easy run of Tendering system.